Pengembangan Sistem Informasi Manajemen Administrasi Perangkat Pembelajaran dan Supervisi Guru pada Sekolah Menengah Kejuruan (SMK) (Studi pada SMK Negeri 5 Malang) - Moh Arif Andrian; Satrio Agung wicak; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The teacher as one of the educational actors has the task and authority to arrange teaching administration, so the learning process can be systematic evaluated. In addition, the teacher also has an obligation to conduct a performance assessment called â€œTeacher Supervisionâ€. In fact, teachers feel burdened due to time constraints, the number of subjects taught and the standard of teaching administration that change frequently. This causes the teachers not willing to arrange teaching administration and it impacts on the constraints of â€œTeacher Supervisionâ€. This study develops a management information system that can assist teachers in arranging learning administration and facilitating the â€œTeacher Supervisionâ€ process. The method used is waterfall, Object Oriented Analysis and Design (OOAD) requirements modeling, and the Model-ViewController (MVC) architecture model. The results showed 17 functionals were declared valid through validation testing, the system went according to the design logic flow through white-box testing and representation of user acceptance assessment of 83.62% through 15 test participants. Based on these results, it can be concluded that the development of Teaching Administration and Teacher Supervision Management Information System can be accepted and work well in Vocational High Schools.